Separating snow and ice melt using water stable isotopes and glacio-hydrological modelling: towards improving the application of isotope analyses in highly glacierized catchments - T. Müller; T. Müller; M. Fischer; M. Fischer; S. N. Lane; B. Schaefli; B. Schaefli; B. Schaefli (The Cryosphere)
Glacio-hydrological models are widely used for estimating current and future streamflow across spatial scales, utilizing various data sources, notably observed streamflow and snow and/or ice accumulation, as well as ablation observations. However, modelling highly glacierized catchments poses challenges due to data scarcity and complex spatio-temporal meteorological conditions, leading to input data uncertainty and potential misestimation of the contribution of snow and ice melt to streamflow. Some studies propose using water stable isotopes to estimate shares of rain, snow and ice in streamflow, yet the choice of the isotopic composition of these water sources significantly impacts results.